Whale watching in Iceland : an assessment of whale watching activities on Skjálfandi bay - Martin, Sara Marie, 1985- (2012)
The whale watching industry has experienced much growth and development throughout the world. In addition to the numerous benefits resulting from this wildlife-based tourism activity, there is also concern that there may be negative impacts on the environment as well. Management has been implemented in many places worldwide to promote what may be more sustainable whale watching practices. In Iceland, where whale watching started in 1991, management is quite limited. There are few guidelines or regulations in place attempting to manage the behaviour of whale watching boats, and the efficacy of the guidelines that do exist is currently unknown. This study utilizes data collected between 2009 and 2011 to assess whale watching activities on Skjálfandi Bay, Northeast Iceland. Both land and boat-based observations were used to monitor three aspects of the whale watching activities: approach density, i.e, the number of boats viewing a particular animal or pod; the distance of approach; and the speed of the approaching boat. The greatest number of boats viewing the same animal or pod was 4, however this was only observed in approximately 4% of the total tracks. The greatest approach density was observed in July of 2009, with an average of 1.95 boats accompanying the animals. The results suggest that the boats are approaching closer to the whales, as an increase in approaches within 50m of the animal(s) was observed between the years, for each species, with exception of the minke whale in 2011. Also in 2011, 24% of the total humpback tracking sessions reveal a boat approached to within 10m, and in 10 tracking sessions to within 4m. The number of boats approaching at higher speeds increased greatly throughout the 300-50m distance range from the animal(s) in 2011. When within 50m, 33% of the tracks revealed boats travelling slower than 2km/hr or idling, the remainder of the boats travelling at speeds ranging up to approximately 17km/hr. The observed approach distances are closer, and the approach speeds greater, than those ...